Arithmetic success and gender-based characterization of brain connectivity across EEG bands. (February 2021) - Demir, Sait; Türker, İlker
Highlights: Functional brain networks employing coherence method is conducted in a comparative manner across EEG bands. Female brain is more connected under rest condition, while male brain boosts connectivity under arithmetic workload. Unsuccessful brains yield more assortative behavior based on beta band networks. Arithmetically successful brains yield greater connectivity under rest condition for most EEG bands. Theta band better diagnoses gender-based differences, while gamma band better discriminates success-based connectivity. Abstract: We provide a distinctive view for rest/task, gender and arithmetic success state for human brain concerning EEG-based functional brain networks. Utilizing coherence method to quantify phase synchronization between EEG nodes, signal activities are converted into graph representations. After a complex-theoretic approach is conducted, intelligent brains emerge as more connected ones under resting state. Male brain, featuring lower connection strength and efficiency under resting state, exhibits the ability to boost up connectivity under mental workload. On the other hand, arithmetic success correlates with high resting state connectivity for all EEG bands but dominantly for gamma band, while unsuccessful brains yield greater beta band assortativity behavior. Theta band associated with unconscious actions apparently exhibits greater connection weights for mental activity compared to resting. Contributions of EEG bands to diagnosing differences in rest/task, gender and arithmetic success states are detailed within the study. We also spot out which connection patterns are related with mental progressing, outlining that intelligent brains yield less inter-frontal and more frontal to central and frontal to parieto-occipital connections.